Pengembangan Lembar Kerja Peserta Didik (LKPD) Teks Negosiasi Berbantuan Aplikasi Power Director pada Siswa Kelas X SMA YPIS. Maju Binjai - Dani Prastika (Universitas Palangka Raya, 2023)
This research is research and development (R&D) which aims to develop negotiation text teaching materials through LKPD assisted by the Power Director Application for Class X YPIS High School students. Maju Binjai which is valid. The development model used is the Borg and Gall model, where in this research the researcher limits development to the development stage. From the stages that have been carried out, the results obtained are that students at YPIS Maju Binjai High School are very interested in using products in learning.